Planning A Digital Transaction System To Maximize The Role Of Village-Owned Enterprises - Pitaloka, Endang; Widiya Avianti; Asyifa, Sarah Laila; Nurramadhan, Delfina; Fadila, Vina Rizki (Universitas INABA, 2025)
Planning a digital sales system that maximizes the role of Village-Owned Enterprises must integrate digital technology to expand market reach, improve operational efficiency, and empower local businesses. This plan includes the use of digital technology in sales systems, digital marketing strategies for Village-owned enterprise, capacity building and collaboration, and identifying the benefits of digital sales systems for Village-owned enterprise. Automation technology offers significant benefits for Village-owned enterprise, ranging from administrative efficiency, market expansion, cost savings, improved service quality, to community empowerment. By adopting automation systems, Village-owned enterprise can increase sales and contribute more significantly to sustainable village economic development. By designing an integrated digital sales system supported by appropriate digital marketing strategies, Village-owned enterprise can maximize their role as drivers of village economic development, increase village income, and strengthen the economic independence of village communities.